2020
DOI: 10.3389/fmicb.2020.596394
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Predictive Function of the Fecal Microbiota Differ Between Young and Adult Donkeys

Abstract: The community of microorganisms inhabiting the gastrointestinal tract of monogastric herbivores played critical roles in the absorption of nutrients and keeping the host healthy. However, its establishment at different age groups has not been quantitatively and functionally examined. The knowledge of microbial colonization and its function in the intestinal tract of different-age donkeys is still limited. By applying the V3–V4 region of the bacterial 16S rRNA gene and functional prediction on fecal samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We also demonstrated that adult female elk age differences can be detected in the microbiome using a 2‐class model. Age‐related differences in the microbiome have been demonstrated in humans and other model animals (Lan et al, 2013; Xing et al, 2020), but evidence in wildlife is still emerging (Xing et al, 2020). Adult age classes undergo microbial succession in response to diverse physiological and environmental forces (Lan et al, 2013; Stephens et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that adult female elk age differences can be detected in the microbiome using a 2‐class model. Age‐related differences in the microbiome have been demonstrated in humans and other model animals (Lan et al, 2013; Xing et al, 2020), but evidence in wildlife is still emerging (Xing et al, 2020). Adult age classes undergo microbial succession in response to diverse physiological and environmental forces (Lan et al, 2013; Stephens et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by better understanding the donkey hindgut microbial ecology, we can inform interventions that can improve animal production performance and host health (4). Previous studies of the equine hindgut microbiome have revealed that the taxonomic composition changes of this bacterial community vary with many factors, including age, breed, diet and disease status (5)(6)(7)(8)(9)(10). However, knowledge about the hindgut microbial ecosystem and metabolism is still lacking despite being essential to host metabolism and health.…”
Section: Introductionmentioning
confidence: 99%
“…Study of the intestinal microbiota of equine genera by traditional culture method has certain limitations ( Milinovich et al, 2006 ), as approximately 70% of the microbiota cannot be cultured in the laboratory, making it difficult to determine the entire microbial composition and largely limiting its application in taxonomy ( Julliand and Grimm, 2016 ; Park et al, 2021 ). The 16S ribosomal RNA (16S rRNA) gene high-throughput sequencing technology, as a novel technical tool for microbial diversity research, is now widely used in animal intestinal flora research, such as Illumina Hiseq-based technology to study different species ( Liu et al, 2020 ), age ( Xing et al, 2020 ), site ( Su et al, 2020 ), and other The structure and diversity of the intestinal microflora under the influence of different factors. In addition, the prediction of intestinal microbial gene function by PICRUSt2 analysis method to further explore the relationship between intestinal flora and host has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%